Assessment of the effectiveness of natural coral fragmentation as a dispersal mechanism for coral reef‐boring sponges. (1st September 2016) - Nava, Héctor; Carballo, José Luis
Abstract: Eastern Pacific reefs are mostly made up of interlocking coral branches of Pocillopora, which are easily broken by physical forces associated with heavy swells and winds. In this study we investigated the potential of these coral fragments to enable propagation of boring sponges. For this, we quantified the frequency of occurrence and diversity of boring sponges in fragments of corals recently trapped among the branches of live colonies, and later tested the hypothesis that these sponges colonize new branches of corals. Nearly 80% of the coral colonies investigated had coral fragments among their branches, and 69% of these coral fragments contained boring sponges (11 species), some of these sponges in reproduction (23% of them carried oocytes). To test whether sponges inhabiting coral fragments could colonize new branching corals we transplanted them to healthy branches, and to branches whose living tissue was mechanically eliminated to simulate damage produced by grazing and death after bleaching and other causes of coral tissue mortality. All the transplanted coral fragments cemented to each new colony by means of calcification, and of the three sponge species tested ( Cliona vermifera, Cliona tropicalis and Thoosa mismalolli ) only C. vermifera was able to colonize both new living branches (26.9%) and cleaned branches (65.5%). The apparent capability of C. vermifera to colonize by direct contact may be another key ability of this species to maintain high frequency of occurrence in Pacific coral reefs. However, although C. tropicalis and T. mismalolli were not able to colonize new coral substrata by direct contact, coral fragments have the potential to contribute to local persistence of these sponges and to their dispersal, both by asexual (fragments) and sexual means (transport of sexual products). The present findings may partly explain the current increase of excavating sponges on deteriorating reefs with a large availability of dead branching corals.